ANALYSIS OF SMALL AND MEDIUM ENTERPRISES ON INCREASING INCOME - Jenny Nancy Kaligis (Journal of International Conference Proceedings (JICP), 2019)
In order to be able to compete every home industry must be able to have good competitiveness. The problem commonly faced by home industry businesses is that they lack extensive marketing networks. Usually the market only deals with the closest consumers. The purpose of this study is that the resulting laundry service products can be accepted by the market or consumers, and have wider market access by utilizing third party services. This qualitative research uses the method of observation and in-depth interviews with laundry business associations in the city of Manado. The results of his research can be concluded that the proliferation of developments in information technology today can actually bring its own blessings to every business actor, depending on whether the business is able to use it or not. Especially for laundry businesses in the city of Manado after several interviews with key informants, it was concluded that the laundry business in the city of Manado is usually located near congested areas such as near campuses where there are many boarding houses there or densely populated areas. In other words, many consumers come from students who live in a dormitory or household whose level of activity is relatively high, so they have less time for their own laundry. Then related to market expansion by using third parties such as online transportation applications, according to the results of interviews, not many laundry businesses use them and consumers don't like using online transportation services. To use online media, only specifically for social media from the laundry business itself as a media campaign.